Synthesis and Crystal Structure of a Trinuclear Aminobis(phenolate) Ytterbium Hydroxide Complex. Issue 6 (2nd June 2016) - Yuan, Fugen; Zhou, Yuan; Li, Li; Qian, Hui
Abstract : The hydrolysis of aminobis(phenolate)lanthanide thiolate of (THF)LYb(SC6 H4 - p -Me) (L 2− = Me2 NCH2 CH2 CH2 N{CH2 -(3, 5- t Bu2 -C6 H2 -2-O − )}2 ) led to the first aminobis(phenolate)lanthanide hydroxide of [(H2 O)LYb(μ-OH)]3 (μ3 -H2 O), being characterized by infrared spectra, elemental analyses, and X-ray crystallography. The product is a novel trinuclear complex, in which three Yb-OH bonds construct a six-membered ring in a chair conformation.